Machine Tools for High Performance Machining - Lopez de Lacalle, Norberto (Springer, 2017)
Machine tools are the main production factor for many industrial applications, in important sectors such as the automotive and aeronautical industry, precision parts, human implants, and mechanical construction. Recent developments in new motion devices and numerical control have lead to considerable technological improvements in machine tools. The use of five-axis machining centers has also spread, resulting in reductions in set-up and lead times. As a consequence, feed rates, cutting speed and chip section have increased, while accuracy and precision have improved as well. Additionally, new cutting tools have been developed, combining tough substrates, optimal geometries and wear resistant coatings. Today’s machines and machining processes are clearly very different to those of the past (...)